The Active Role of Santri in Creating an Inspiring Learning Environment: Peran Aktif Santri dalam Mewujudkan Lingkungan Belajar Inspiratif - Lubis, Alam; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic boarding schools play a crucial role in shaping students’ character and academic growth. Specific Background: However, the motivation of students in these institutions can decline due to monotonous teaching methods and limited program innovations. Knowledge Gap: Previous studies have rarely provided a comprehensive analysis combining causal factors, implemented efforts, existing challenges, and future strategic plans to sustain students’ learning motivation in pesantren settings. Aims: This study aims to identify the causes of decreased motivation, evaluate current improvement efforts, explore challenges, and outline future plans to strengthen learning motivation among santri. Results: Findings reveal key causes, including limited teaching variety, monotonous programs, and insufficient parental support. Current initiatives involve consistent guidance, strict discipline, regular monitoring, and beneficial additional programs. Challenges include uncontrollable student behavior, lack of parental involvement, and limited teacher competence. Planned programs focus on service and facility improvement, comparative studies, and inviting educational motivators. Novelty: This study integrates a multi-dimensional perspective—causes, solutions, challenges, and strategic plans—into a single framework for pesantren motivation improvement. Implications: The findings offer practical recommendations for pesantren management to create more dynamic, student-centered learning environments that foster sustained motivation and educational quality.Highlights : Comprehensive analysis of causes, solutions, challenges, and future plans in pesantren. Strategic recommendations for sustaining student motivation and learning quality. Multi-dimensional approach combining educational, managerial, and social perspectives. Keywords: Santri, Learning Motivation, Islamic Boarding School, Educational Strategies, Student Engagement